A desigualdade socioespacial expressa pelas variáveis do sistema de informação sobre nascidos vivos em três municípios da região metropolitana de Maringá - Paraná, 2006 - Predebon, Kelen Marja (2009)
Analyzing the changes regarding the indicators of the maternal infantile health contributes to evaluating either the forward or backward events of the access and accessibility in health as for indicating possible health care inequalities and helping the planning of actions. In this process, the spatial analysis of data on health, geoprocessing, is an important tool for detecting inter- and intra-urban variations. The Information System on Alive-Born Children (Sinasc) is a relevant source to geovaried studies and gathers a data range related to the mother, pregnancy and delivery, and the newborn baby. This study aimed at spatially analyzing the characteristics of the births in the municipal cities of Maringá, Sarandi and Paiçandú-Pr through the variables of Sinasc. It is an ecological and exploratory study. The analyzed population was all those alive-born babies registered in Sinasc in 2006, children from mothers living in the 3 studied cities. The analysis unit was the Demographic Expansion Area (AED) and the space consisted of 19 AEDs. For the spatial distribution and self-correlation through the global and local Moran Index (LISA) the following variables were analyzed: mother's age, mother's schooling and race/color, defined as social economic variables. Moreover, the number of prenatal appointments and Caesarean births were analyzed; defined as health care variables. Considered as resulting variables, weight of the born baby, pregnancy length and apgar in the 5th minute were analyzed. Afterwards, the resulting variables were associated with social economic and health care variables through the application of the qui-quadrado statistic test at a significant level of 5%. This association happened in every area of the social occupational type, a methodology proposed by the research group from Metropolis Observatory Maringá Chapter which characterizes and analyzes the space social dynamics by social economically gathering the similar AEDs in 6 types. The spatial distribution of the social economic variables showed concentration in the periphery AEDs, particularly in Sarandi and Paiçandú, with a meaningful spatial self-correlate index in the 3 variables. The health care variables were less concentrated with a higher value of Caesarean births in the central AEDs 32 in Maringá and a small number of prenatal appointments slightly higher in the AEDs in Sarandi, an area that showed some meaningful spatial self-correlation. As for the resulting variables the spatial distribution was at random with a slight concentration of low apgar at 8 in the AEDs in Sarandi, the only one with meaningful spatial self-correlation. In the variables association there was significant statistics of pregnancy length with the number of prenatal appointments in the 6 areas of the social occupational type. The weight also showed significant statistics when associated with the number of prenatal appointments in every area, except for in the higher area of the social occupational type with better social economic levels. The association of the apgar with the number of prenatal appointments was also significant in every area, except for, again, in the Higher area. Although the general indexes present good maternal infantile health indicators, the variations among the several population segments remain high, addressing the discussions arisen by analysis of the social occupational type in which the space is socially segregated with the concentration of the best indicators in the central areas. The association of the resulting variables with the number of prenatal appointments point to the relevance of the health service in obtaining satisfactory results of pregnancies and births. This academic research has to be looked as an exercise in relation to the presented techniques and aims to animate a more extensive debate about the issues related to inequalities in health in the maternal infantile subject, also helpful to planning, in the health care services in the analyzed geographic area.